Challenges Linked to Post-Polio-Paralysis in Khyber Pakhtunkhwa Region - Khan, Muhammad Kamran; Khan , Alamgeer (Poltekkes Kemenkes Jakarta I, 2024)
Background: Poliomyelitis is a highly infectious viral disease often causing permanent paralysis. Post-Polio Paralysis (PPP) involves the delayed onset of new or worsening neuromuscular symptoms years after the initial attack. Polio survivors face numerous physical disabilities and significant social, financial, and human rights barriers. Aims: To identify the challenges faced by individuals with PPP in the Khyber Pakhtunkhwa region. Methods: The study employed a cross-sectional survey design with a sample size of n=200, selected through non-probability convenience sampling. Data were collected using the Post-Polio Clinic Questionnaire and analyzed with SPSS 22. Results: The gender distribution was 21.50% female and 78.50% male. New health and physical problems (neurological, arthritis, and physiological) were observed in 64.5% (n=129) of participants. Aggravated previous complications, such as pain, fatigue, and muscular atrophy, were reported by 91.5% (n=183). Difficulty performing heavy tasks was noted by 49.5% (n=99). Using public transport was a challenge for 46.5% (n=93), and driving a car was deemed impossible by 70% (n=140). Using an Indian commode as a toilet was a complication for 58% (n=116) of participants. Conclusion: The study reveals significant health and daily life challenges for polio survivors in Khyber Pakhtunkhwa, including a high prevalence of new and worsening neuromuscular symptoms, aggravated complications like pain and fatigue, and difficulties with heavy tasks, public transport, driving, and using certain toilets. These findings underscore the urgent need for targeted interventions to improve the quality of life for polio survivors by addressing their physical health and social and financial barriers.